Identification and Purification of Cholera Like Toxin from Environmental Isolate of Vibrio cholerae - Baghdad Science Journal (مجلة بغداد للعلوم)
The presence and prevalence of V. cholerae were investigated in forty five water samples collected from different locations of Tiger River/ Baghdad city. Twenty one isolates were isolated by adopting a simple isolation techniques. The final identification revealed that only three isolates were confirmed as V. cholerae. They were named 1J, 1R and Dial 131 which are all serogrouped as non-O1. Toxin Coregulated Pili (TCP) and heat labile enterotoxin (LT) were determined in only the environmental isolate 1J while non of the isolates produced heat stabile toxin (ST). The purification scheme was improved, few steps were adopted to include back extraction of ammonium sulfate, saturation between 80-20%, desalting through Sephadex G25, and gel filtration using Sephadex G100 which highly increase the specific activity.